Waste Foundry Sand Usage for Building Material Production: A First Geopolymer Record in Material Reuse - Neslihan Doğan-Sağlamtimur (Advances in Civil Engineering)
In order to bring a solution to the problem of waste foundry sand (WFS) in the foundry sector and achieve its reuse, geopolymer building material (as a cementless technology) was produced from the WFS for the first time in the literature in this study. The physical and mechanical characteristics of this material were determined. In the first part of the experimental step, the sieve analysis, loose/tight unit weight, and loss of ignition of the WFS were obtained as well as the ultimate analysis. In the second step, the water absorption percentage, porosity, unit weight, and compressive strength tests were conducted on the WFS-based geopolymer specimens activated by chemical binders (sodium hydroxide: NaOH and sodium silicate: Na2SiO3). As the unit weights of all the produced samples were lower than 1.6 g/cm3, they may be considered as lightweight building materials. The minimum compressive strength value for building wall materials was accepted as 2.5 MPa by national standards. In this study, the maximum compressive strength value was measured as 12.3 MPa for the mixture incorporation of 30% Na2SiO3 at the curing temperature of 200°C in 28 days. It was concluded that this geopolymer material is suitable for using as a building wall material.